UMBILICAL CORD CORTISOL LEVELS IN NEWBORNS DEPENDING ON GENDER AND MODE OF DELIVERY - Martinovska, Iskra; Gucheva, Nevenka Laban; Timovska, Silvana Naunova; Izairi, Pranvera; Kocevska, Ana (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
One of the most stressful experiences for a newborn is the act of childbirth, and multiple researchers confirmed increased levels of cortisol and catecholamines in the blood of the newborn immediately after spontaneous vaginal delivery (SVD). In contrast, completing the birth by elective cesarean section (SC) should be far less stressful for the newborn, presenting with lower cortisol levels. Prospective clinical study measuring serum cortisol levels in umbilical cord blood samples was conducted at the Mother Teresa Hospital in Skopje, and 88 samples were obtained for analysis. The aim was to compare cortisol levels in healthy and appropriate for gestational age (AGA) newborns, depending on gender and mode of delivery. The results showed a mean cortisol level of 93.41 [95%CI 82.72 – 104.10]. In those born with SVD, the mean cortisol level was higher with a mean value of 118.13 [95%CI 102.77 – 133.50], and was significantly higher than in those born with SC in which the mean cortisol level was with a mean value of 70.83 [95%CI 59.19 – 82.47], with a statistically significant difference (p<0.0001). There was no significant difference between cortisol levels when grouping was done by gender (p=0.424). According to the results and comparative literature, we can say that the level of cortisol in the umbilical cord, as well as its dependence on the method of delivery, can be a good early indicator of the stress experienced during pregnancy and the birth process. Keywords:    cortisol ,  newborn ,  umbilical cord ,  delivery ,  gender.